PERUBAHAN KLIMATOLOGIS CURAH HUJAN DI DAERAH ACEH DAN SOLOK - Juniarti Visa (Jurnal Sains Dirgantara, 2005)
The analysis of rainfall climatologic change of Aceh and Solok area using 103 years (1900-2003) data for wet season (DJF) and dry season (JJA) have been done. The result show that for Aceh area, for wet season (DJF) the maximum rainfall was 664 mm/month in 1926, which was in the normal condition. And for dray season (JJA) the rainfall condition for periods JJA-7. (1961-1990), JJA-8 (1971-2000) and JJA-9 (1981-2003) were under normal condition. For Solok area the maximum rainfall was 1972 mm/mounth in 1972, the rainfall condition for wet season (DJF) and dry season (JJA) are in the normal condition.